Dynamics of Complex Interconnected Systems: Networks and Bioprocesses - Skjeltorp, Arne T.; Belushkin, Alexander V.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
The book reviews the synergism between various fields of research that are confronted with networks, such as genetic and metabolic networks, social networks, the Internet and ecological systems. In many cases, the interacting networks manifest so-called emergent properties that are not possessed by any of the individual components. This means that the detailed knowledge of the components is insufficient to describe the whole system. Recent work has indicated that networks in nature have so-called scale-free characteristics, and the associated dynamic network modelling shows unexpected results such as an amazing robustness against accidental failures. Modelling the signal transduction networks in bioprocesses as in living cells is a challenging interdisciplinary research area. It is now realized that the many features of molecular interaction networks within a cell are shared to a large degree by the other complex systems mentioned above, such as the Internet, computer chips and society. Thus knowledge gained from the study of complex non-biological systems can be applied to the intricate braided relationships that govern cellular functions.
STRUCTURE AND COMMUNICATION IN COMPLEX NETWORKS -- EFFECTS OF COMMUNITY STRUCTURE ON SEARCH AND RANKING IN COMPLEX NETWORKS -- THE SOS RESPONSE OF BACTERIA TO DNA DAMAGE -- SELF-AFFINE SCALING DURING INTERFACIAL CRACK FRONT PROPAGATION -- DIFFUSION, FRAGMENTATION AND MERGING PROCESSES IN ICE CRYSTALS, ALPHA HELICES AND OTHER SYSTEMS -- MOLECULAR MECHANISMS IN BIOSIGNALLING: VISUAL RECEPTION -- THE ARCHITECTURE OF COMPLEXITY: FROM WWW TO CELLULAR METABOLISM -- MATHEMATICAL MODELING OF NEURAL ACTIVITY -- BRAIDED SPACE-TIME PARTICLE NETWORKS -- COMBINING OPTICAL TWEEZERS AND MICROPIPETTES FOR DNA STRETCHING: ELASTICITY OF MICROPIPETTE CRUCIAL -- UNIVERSAL NETWORKS AND PROCESSES IN SOFT AND COMPLEX MATTER: FROM NANO TO MACRO -- WHAT ECONOMISTS SHOULD LEARN FROM ECONOPHYSICS -- THE MINORITY GAME: STATISTICAL PHYSICS OF COLLECTIVE BEHAVIOUR OF ADAPTIVE AGENTS IN A COMPETITIVE MARKET.
Keywords: PHYSICS; SOFT CONDENSED MATTER; BIOMEDICAL ENGINEERING; ENGINEERING; SOCIAL SCIENCES; BIOMATERIALS; PHYSICS; COMPLEXITY; SOFT MATTER, COMPLEX FLUIDS; BIOPHYSICS/BIOMEDICAL PHYSICS; BIOMATERIALS; SOCIAL SCIENCES, GENERAL